THE CONCEPTS OF GEOGRAPHICAL STUDIES OF RA FRONTIER, MOUNTAINOUS AND HIGH MOUNTAINOUS AREAS SETTLEMENT PATTERN (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The research of RA frontier, mountainous and high mountainous areas settlement pattern, revelation and solution of current problems is one of the ways of effective use of territorial and human potential of such regions. The concepts of geographical survey of RA frontier, mountainous and high mountainous areas settlement pattern are discussed in the article. The issues of settledness, population and settlements distribution symmetry and diffusion, settlement pattern territorial structure and dynamics, population number of settlements, demographical situation and current problems, also the interaction issues of settlement territorial structure and administrative-territorial division are highlighted in the article.
Keywords: settlement pattern; frontier areas; mountainous and high mountainous areas; population number; settledness; settlement territorial structure; settlement dynamics